Suppression of long-distance movement of tobacco etch virus in a nonsusceptible host. - Schaad, M C (1996)
To investigate host functions involved in the tobacco etch potyvirus (TEV) infection process, a tobacco line (V20) with a strain-specific defect in supporting systemic infection was analyzed. Using a modified TEV encoding a reporter protein, beta-glucuronidase (GUS), genome amplification, cell-to-cell movement, and long-distance movement were measured in V20 and a susceptible line, Havana425. Comparable levels of TEV-GUS genome amplification were measured in inoculated protoplasts from both tobacco lines. The rates of cell-to-cell movement of virus in inoculated leaves were nearly identical in V20 and Havana425 between 48 and 72 h postinoculation. In contrast, long-distance movement from leaf to leaf was markedly restricted in V20 relative to Havana425. In situ histochemical analysis of inoculated leaves revealed that infection foci expanded radially over time, providing the potential for contact of virus with veins. Immunocytochemical analysis of V20 tissue from infection foci indicated that TEV-GUS entered the phloem parenchyma or companion cells adjacent to the sieve elements, suggesting that the block in long-distance movement was associated with entry into, or exit from, sieve elements. The genetic basis for the V20 restriction was characterized in a segregation analysis of a cross between V20 and Havana425. The heterozygous F1 progeny displayed the susceptible phenotype, indicating that the V20 restriction was a recessive trait. Segregation in the F2 progeny indicated that the restriction was likely due to the interaction of recessive genes at two nonlinked loci. These data support the hypothesis that long-distance movement requires a set of host functions that are distinct from those involved in cell-to-cell movement.